When Discounts Hurt Sales: The Case of Daily-Deal Markets - Cao, Zike; Hui, Kai-Lung; Xu, Hong (Information Systems Research, 2018)
We investigate whether the discounts offered by online daily deals help attract consumer purchases. By tracking the sales of 19,978 deals on Groupon.com and conducting a battery of identification and falsification tests, we find that deep discounts reduce sales. A 1% increase in a deal’s discount decreases sales by 0.035%–0.256%. If a merchant offers an additional 10% discount from the sample mean of 55.6%, sales could decrease by 0.63%–4.60%, or 0.80–5.24 units and 42–275 in revenue. This negative effect of discount is more prominent among credence goods and deals with low sales, and when the deals are offered in cities with higher income and better education. Our findings suggest that consumers are concerned about product quality, and excessive discounts may reduce sales immediately. A follow-up lab experiment provides further support to this quality-concern explanation. Furthermore, it suggests the existence of a “threshold” effect: the negative effect on sales is present only when the discount is sufficiently high. Additional empirical analysis shows that deals displaying favorable third-party support, such as Facebook fans and online reviews, are more susceptible to this adverse discount effect. We draw related managerial implications. The online appendix is available at https://doi.org/10.1287/isre.2017.0772 .